Gerakan Puritanisme Persatuan Islam di Kepulauan Sapeken-Sumenep Madura, 1972-2016 - Nurul Fatimah (UIN Sumatera Utara Medan, 2018)
This study focuses on the discussion of puritanisme movement in Sapeken islands Sumenep-Madura. As it is known that the area of Madura is a very loyal tradisional Islamic support base. But especially in the Sapeken islands, the puritanical Islamic can actually thrive. The purpose of this study is to know the process of development of the puritanitanism movement (Persis). This study also attempts to answer the question of why puritanical islamic is capable of developing in the Sapeken islands. Using the protestant ethic of Max Weber, it can be seen that the entry of the puritanism movement (Persis) is base on the socio-religious conditions of society which are still considered far from the pure Islamic teachings. Therefore (Persis) perform purification of tradisional Islamic traditions and lokal art that still contains elements of takhayul, bid`ah dan khurafat, with the aim of returing the ummah to the teachings of the qur`an and sunnah. Throgh education institutions, Persis instilling a puritan ideology to the people, in addition, Persis in the Sapeken islands became more dominant religious organization, evident from the development of more rapid educational institutions due to the high work ethic of puritan muslims (Persis).